2022
DOI: 10.3844/ojbsci.2022.323.332
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Soil Salinity on the Growth and Development of Maize (Zea Mays L.) by using Sentinel-2 Imagery

Abstract: Salinization of soil cover and the constant increase in their area have become one of the most pressing problems year after year for irrigated agriculture regions. The degradation processes caused by the salinity of soils negatively affect the growth and development of food crops. Therefore, this study focused on the effects of soil salinity in the midstream of the Syrdarya on the growth and development of maize where the climate is continental and mostly arid, and the cultivation of crops is possible under ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The spectral channels of the Sentinel-2 satellite, taken on July 28, were used to calculate this index. In previous studies [Laiskhanov et al, 2022], it was found that the greenest period of corn grown on non-saline soils corresponds to July 28, and it is much later on saline soils. Salinity slows down the growth and development of corn during the growing season.…”
Section: Mapping Of Soil Salinity Using Remote Sensing -The Case Of C...mentioning
confidence: 91%
See 3 more Smart Citations
“…The spectral channels of the Sentinel-2 satellite, taken on July 28, were used to calculate this index. In previous studies [Laiskhanov et al, 2022], it was found that the greenest period of corn grown on non-saline soils corresponds to July 28, and it is much later on saline soils. Salinity slows down the growth and development of corn during the growing season.…”
Section: Mapping Of Soil Salinity Using Remote Sensing -The Case Of C...mentioning
confidence: 91%
“…With the rapidly population density growth has increased anthropogenic impact, and a combination of climatic features leads to increased salinity and pollution of irrigated soils in this region, resulting soil salinization has become the main restraint for a Mapping of Cornfield Soil Salinity in Arid and Semi-Arid Regions crop production and regional ecosystems [Suska-Malawska et al, 2022]. The Shaulder irrigated massif in the middle reaches of the Syr Darya river, where irrigated lands are most widely used for cornfields, the degree of soil salinity is different and it has been determined that they increase with depth [Laiskhanov et al, 2022]. In determining of the soil salinity in the cornfields, first carried out the division of cornfields, for this, vegetation phenological dynamics were characterized using a time series of vegetation indices derived obtained from satellite data, mainly the Normalized Difference Vegetation Index (NDVI), as a result, the difference in the growth phase of corn and other crops was determined [Jin and Xu, 2013;Segarra et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other agricultural areas of the south, Otyrar is well provided with water resources. However, due to inefficient use and the management of water resources, groundwater rises and contributes to soil salinization [45], this threatens the overall sustainability of the crop farming system on irrigated and dry land [20]. The fields in the study area are irrigated once in early spring using flood irrigation, and in summer, it is watered 2-3 times before the end of the vegetation period using the furrow irrigation method.…”
Section: Description Of the Study Areamentioning
confidence: 99%